2011
DOI: 10.1371/journal.pone.0024983
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Locus Variable-Number Tandem Repeat Profiling of Salmonella enterica Serovar Typhi Isolates from Blood Cultures and Gallbladder Specimens from Makassar, South-Sulawesi, Indonesia

Abstract: Multi-locus variable-number tandem repeat analysis differentiated 297 Salmonella enterica serovar Typhi blood culture isolates from Makassar in 76 genotypes and a single unique S. Typhi genotype was isolated from the cholecystectomy specimens of four patients with cholelithiasis. The high diversity in S. Typhi genotypes circulating in Makassar indicates that the number of carriers could be very large, which may complicate disease prevention and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…The predominant alleles of TR1 loci revealed a repeat number of 5 among the study isolates, which was also shown in earlier studies among S. Typhi Indian isolates (31,33). The range of number of repeats and prevalent alleles in VNTR loci was found to vary in S. Typhi isolates from different geographical locations (10,23,28). None of the 6 VNTR loci was found to contain zero-repeat copy in any of the study strains (Table 2).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The predominant alleles of TR1 loci revealed a repeat number of 5 among the study isolates, which was also shown in earlier studies among S. Typhi Indian isolates (31,33). The range of number of repeats and prevalent alleles in VNTR loci was found to vary in S. Typhi isolates from different geographical locations (10,23,28). None of the 6 VNTR loci was found to contain zero-repeat copy in any of the study strains (Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…Compared to PFGE, MLVA has been adopted by several European countries for epidemiological investigations of nontyphoidal S. enterica serovars, including Typhimurium and Enteritidis, due to its cost-effectiveness, rapid turnaround time, and ease of inter-laboratory comparison of results (30). Nevertheless, for S. Typhi, the MLVA typing method is still under evaluation (10,28,23). The present study examined the discriminatory ability of MLVA typing with respect to PFGE and antimicrobial resistance profiles of S. Typhi (n = 66) circulating in India during 2007-14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown that Salmonella respond rapidly in vitro to growth in gallbladder mimicking conditions, increasing biofilm formation and antimicrobial resistance in the presence of bile [19], and altering expression of fimbrial and outer membrane proteins in response to growth in bile and on cholesterol substrates [21, 22]. Recent clinical evidence supports the notion of ongoing bacterial adaptation to the gallbladder environment; with clinical isolates from gallbladder carriers exhibiting a common genetic profile distinct from those of isolates infecting other sites of the body [23], potentially implying a specific S . Typhi genotype associated with preferential infection of gallbladder.…”
Section: The Mechanisms Of Salmonella Persistence In the Gallbladdermentioning
confidence: 99%
“…The clinical symptoms as severity of illness like stupor, melena and perforation in carrier state of typhoid fever has related with flagellin genes variants especially Hd Several studies suggested that flagellin genes variants of Hj + association of decreased severity of illness, motility and invasiveness of bacteria and compared with flagellin genes variants of Hd + [10] and flagellin genes variants of z66Ind + might seems related with severity of illness of typhoid fever [19]. It is supported by our results that flagellin genes variants of Hd + z66Ind…”
Section: Discussionmentioning
confidence: 99%